Предмет: Алгебра,
автор: needer
(cosx+sinx)/cosx-sinx=tg2x+cos^-1(2x) докажите тождество
Ответы
Автор ответа:
0
Будем работать с правой часть уравнения
Автор ответа:
0
(cosx+sinx)/(cosx-sinx) = tg2x + 1/cos2x
(cosx+sinx)/(cosx-sinx) = sin2x/cos 2x + 1/cos2x
(cosx+sinx)/(cosx-sinx) = (sin2x + 1)/cos 2x
(cosx+sinx)/(cosx-sinx) = (sin2x + sin²x + cos²x)/cos 2x
(cosx+sinx)/(cosx-sinx) = (sinx + cosx)²/(cos²x - sin²x)
(cosx+sinx)/(cosx-sinx) = (sinx + cosx)·(sinx + cosx)/(cosx - sinx)(sinx + cosx)
(cosx+sinx)/(cosx-sinx) = (sinx + cosx)/(cosx - sinx)
(cosx+sinx)/(cosx-sinx) ≡ ( cosx + sinx)/(cosx - sinx)
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: esetdidisheva
Предмет: Литература,
автор: Ирчик1999